The socio-religious role of witchcraft in the Old Testament culture: an African insight - Fabian, Dapila N. (Old Testament essays, 1998)
In this paper, the methodological question of why conclusions regarding ancient Near-Eastern (and specifically, Israelite) witchcraft practices cannot be made using contemporary African analogies, is brought to issue. After offering arguments to substantiate his choice of method, the author continues to descriptionbe principles underlying African witchcraft practices, and to match certain Old Testament and other ancient Near-Eastern examples (notably those taken from the Akkadian Maql texts) to these. Ancient Israel's social structure, the changes within it with regard to the position of its lowly and downtrodden members, and the function witchcraft came to fulfil within this changed structure, are then taken into consideration.